2009
DOI: 10.4103/0028-3886.59481
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of a pineal papillary glioneuronal tumor with extensive ventricular involvement: Case report with review of literature

Abstract: Papillary glioneuronal tumor (PGNT) is a newly described mixed glioneuronal tumor, recently included in the World Health Organization classification of central nervous system tumors. We report morphologic and immunohistochemical characteristics PGNT of the pineal region extending into the third and lateral ventricles in a four-year-old male child and reviewed all the cases reported in the international literature till date. In this child the diagnosis of PGNT was established by endoscopic biopsy and squash sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The observed degenerative changes were previously reported with variable frequencies. 4 Immunohistochemically, the biphasic pattern appreciated in ordinary sections was reflected by positive immunostaining for both glial and neuronal markers, which was seen in respective glial and neuronal areas without dual expression. Similar results were reported by a recent study that observed either astrocytic or neuronal differentiation, without any hybrid cells.…”
Section: Discussionmentioning
confidence: 99%
“…The observed degenerative changes were previously reported with variable frequencies. 4 Immunohistochemically, the biphasic pattern appreciated in ordinary sections was reflected by positive immunostaining for both glial and neuronal markers, which was seen in respective glial and neuronal areas without dual expression. Similar results were reported by a recent study that observed either astrocytic or neuronal differentiation, without any hybrid cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 89 cases of PGNT have been reported in the English literature . Radiologically, most of these cases showed a cystic mass with a mural nodule in the periventricular location.…”
Section: Discussionmentioning
confidence: 99%
“…Husain et al recently reported a case involving a 4-year-old child with obstructive hydrocephalus with a tumor involving the pineal gland and the ventricular system (Table 1) [8] without anaplastic features or high vascularity. It seems that glioneuronal tumors in the pineal gland may occur in any group, with older patients having a greater predilection for anaplasic features (Table 2), however the number of cases is too small to postulate this trend.…”
Section: Discussionmentioning
confidence: 99%